Application of indigenous knowledge to flood prevention and management (2012)
"In the last three decades, flooding has become a nightmare associated with rainfall in all the continents of the world, as it records heavy casualties everywhere and each time it occurred. Flooding is now a big and seemingly unstoppable environmental threat to rural and urban settlements, in both developed and developing countries, regardless of their topographic traits (mountainous or lowland) and locations (coastal or landlocked). It is no longer limited to coastal communities, such as Vancouver, Bangkok and Manila or Lagos, Port-Harcourt, Warri, Sapele, Calabar, and Yenagoa in Nigeria, as many residents of landlocked cities, towns, and villages have been killed and properties destroyed by flash flood. Flooding has Significantly impacted peoples' housing, transportation, electricity, water and sanitation infrastructure, food and livelihood security. Engineering measures to address the effects of flooding through the provision of hydraulic structures seem inadequate. Indigenous knowledge (IK) has been practiced in rural communities over time to address disasters and it has been found to be effective in the protection of the lives and properties of the people and communities. This paper examines the application of indigenous knowledge to flood control and management in urban and rural communities in different parts -of the world. It reviews the traditional rain prediction and flood control mechanisms as well as the coping and adaptation strategies practiced in the communities as reflected in their IK. The paper argues that it is imperative to augment western flood control practices with indigenous load prediction and management skills to achieve sustainable flood prevention and control."